Sea lice (Lepeophtheirus salmonis) life stage impacts atlantic salmon transcriptomic responses under different thermal profiles - Ghanei-Motlagh, Reza; Cai, Wenlong; Poley, Jordan D.; Whyte, Shona K.; Garber, Amber F.; Fast, Mark D. (Frontiers in Genetics, 2025)
Sea lice (Lepeophtheirus salmonis) infestation continues to pose a persistent and escalating challenge to the global salmon aquaculture industry. Given the complexity of host-parasite interactions, family-based transcriptomic studies provide crucial insights into genetic variation in host responses to sea lice, potentially guiding the development of selective breeding programs to manage parasite resistance in Atlantic salmon. This study investigated global gene expression (transcriptomic) responses of the skin and head kidney of Atlantic salmon (Salmo salar) from different families following infestation at two distinct stages of sea lice, chalimus II and adult, under varying temperature conditions (10°C and 20°C). RNA sequencing results revealed consistent expression of lice-responsive genes across different families under varying thermal conditions, which allowed the identification of potential biomarkers associated with adult-stage compared to chalimus-stage infestations. Our findings highlight critical physiological disruptions in salmon infested with advanced (adult) stages of lice, including uncontrolled and persistent inflammation, dampened/dysregulated immune responses, and impaired tissue repair at attachment sites. This study provides a comprehensive analysis of the transcriptomic responses of Atlantic salmon to different developmental stages of sea lice under specific temperature conditions (10°C and 20°C), and identifies several novel molecular markers from RNA-seq analysis that may be instrumental in developing targeted control strategies for this economically important parasite.